Optimized BCMA/CS1 bispecific TRuC-T cells secreting IL-7 and CCL21 robustly control multiple myeloma - Li, Min; Zheng, Rong; Liu, Zairu; Zhang, Peiyuan; Zhu, Tingwei; Xin, Xueyi; Zhao, Hongli; Chen, Wenyi; Zheng, Binjiao; Zhao, Ai; Gao, Jimin (Frontiers in Immunology, 2024)
IntroductionChallenges remain in reducing antigen escape and tumor recurrence while CAR-T cell therapy has substantially improved outcomes in the treatment of multiple myeloma. T cell receptor fusion construct (TRuC)-T cells, which utilize intact T cell receptor (TCR)-CD3 complex to eliminate tumor cells in a non-major histocompatibility complex (MHC)-restricted manner, represent a promising strategy. Moreover, interleukin-7 (IL-7) is known to enhance the proliferation and survival of T cells. C-C motif chemokine ligand 21 (CCL21) is a ligand for chemokine C-C motif receptor 7 (CCR7) and exhibits strong chemotaxis against naïve T cells and antigen-presenting cells such as dendritic cells.MethodsThe bispecific TRuC-T cells simultaneously targeting B cell maturation antigen (BCMA) and CD2 subset 1 (CS1) were constructed by pairing two of five subunits (i.e., TCRαC, TCRβC, CD3γ, CD3δ, and CD3ϵ) in the TCR/CD3 complex and were named C-AC-B-3E, C-BC-B-3E, C-3G-B-3E, C-3D-B-3E, C-3E-B-3E, B-3E-C-3E, B-3G-C-3E, and B-3D-C-3E. Additionally, the BCMA/CS1 bispecific TRuC-T cells secreting IL-7 and CCL21, named BC-7×21 TRuC-T cells, were generated. All of the bispecific TRuC-T cells were characterized and tested in vitro and in vivo.ResultsFollowing the optimization of various pairs of two subunits of TCR/CD3 complex, B-3G-C-3E TRuC-T cells, characterized by incorporating CD3γ and CD3ε, exhibited the strongest myeloma-specific cytotoxicity. Furthermore, the bispecific BC-7×21 TRuC-T cells had stronger proliferation, chemotaxis, and cytotoxicity in vitro. Accordingly, the bispecific BC-7×21 TRuC-T cells showed better persistence in vivo so as to effectively suppress tumor growth in the NCG mouse xenograft model of MM.1S multiple myeloma.DiscussionThis study demonstrated that BC-7×21 TRuC-T cells, engineered through the optimization of the two subunits of TCR/CD3 complex and a co-expression cytokine strategy, may offer a novel and effective therapy for relapsed/refractory multiple myeloma.